2022
DOI: 10.1186/s12974-022-02470-6
|View full text |Cite
|
Sign up to set email alerts
|

Adamantinomatous craniopharyngioma cyst fluid can trigger inflammatory activation of microglia to damage the hypothalamic neurons by inducing the production of β-amyloid

Abstract: Introduction The mechanism by which adamantinomatous craniopharyngioma (ACP) damages the hypothalamus is still unclear. Cyst fluid rich in lipids and inflammatory factors is a characteristic pathological manifestation of ACP and may play a very important role in hypothalamic injury caused by tumors. Objective The objective of this study was to construct a reliable animal model of ACP cyst fluid-induced hypothalamic injury and explore the specific m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…The damage to the VMH or arcuate nucleus predominantly contributes to extreme energy imbalance and progressive weight gain [ 33 ]. In addition to physical impairment, a study also found that adamantinomatous craniopharyngioma oily fluid may cause obesity by triggering inflammatory activation of microglia and damage to hypothalamus neurons [ 34 ]. Therefore, minimizing the damage to the hypothalamus caused by surgery is crucial for stable postoperative weight.…”
Section: Discussionmentioning
confidence: 99%
“…The damage to the VMH or arcuate nucleus predominantly contributes to extreme energy imbalance and progressive weight gain [ 33 ]. In addition to physical impairment, a study also found that adamantinomatous craniopharyngioma oily fluid may cause obesity by triggering inflammatory activation of microglia and damage to hypothalamus neurons [ 34 ]. Therefore, minimizing the damage to the hypothalamus caused by surgery is crucial for stable postoperative weight.…”
Section: Discussionmentioning
confidence: 99%
“…This senescent phenotype could be the cause (or the consequence) of shortened telomeres that have been observed in ACPs harboring mutations as compared to their counterparts that do not harbor mutations [ 50 ]. A recent study showed that, in addition to the mass effect exerted by the tumor, the hypothalamic sequelae of ACPs could also result from a direct and detrimental effect of inflammatory factors contained in the tumor cyst [ 51 ]. As such, by injecting human ACP cyst fluid into the bilateral hypothalamus of mice, growth retardation and increased obesity occurred together with a decreased expression of genes involved in growth regulation and energy metabolism in hypothalamic neurons.…”
Section: Molecular Landscape Of Craniopharyngiomasmentioning
confidence: 99%
“…As such, by injecting human ACP cyst fluid into the bilateral hypothalamus of mice, growth retardation and increased obesity occurred together with a decreased expression of genes involved in growth regulation and energy metabolism in hypothalamic neurons. Eventually, β-amyloid deposition, a marker of neurodegenerative diseases, was also observed in the hypothalamic area of injected mice [ 51 ]. The immune system appears to also play a role in the pathogenesis of ACPs, as evidenced by the release of immunosuppressive factors, such as IL-10, in the ACP cyst fluid [ 48 ].…”
Section: Molecular Landscape Of Craniopharyngiomasmentioning
confidence: 99%
“…Craniopharyngioma (CP) is a benign slow growing (WHO grade 1) sellar/suprasellar neoplasm that arises from the epithelial remnants in the anterior part of Rathke pouch at the infundibular stalk juncture with pituitary gland [ 45 ]. According to the 2021 WHO classification, CPs include two distinct entities, adamantinomatous CP (ACP) and papillary CP (PCP), formerly considered only subtypes, given that now is known that they exhibit different clinical and molecular features [ 46 ], and will be therefore discussed separately.…”
Section: Introductionmentioning
confidence: 99%